The Relationship Between Maximal Oxygen Intake, Body Fat and Bone Marker Measurements in Different Sports Branches - Serap Demir; Armağan A. Yürük (Hacettepe University, 2017)
Objectives: The purpose of our study is to evaluate the interaction between maximal oxygen intake, body composition and some bone marker measurements in Turkish elite players. Methods: A total of 51 Turkish players of Turkish Super League from following disciplines were included in the study: football (25 players), basketball (12 players) and volleyball (14 players). Maximal oxygen intake as a cardiorespiratory fitness measurement and some anthropometric measurements such as body weight, fat mass, fat free mass were measured. We analyzed the serum samples for total serum 25(OH)D and calcium levels. The data of individuals were categorized as indoor sports (volleyball and basketball) and outdoor sports (football); also according to the branches. Results: In this study, it was found that, fat mass (p=.019) and fat free mass (p=.000) were significantly higher for indoor sports athletes. On the contrary, VO2 max intake (p=.001) and serum vitamin 25(OH)D (p=.000) levels were significantly lower in indoor athletes. For all participants, only 51.0% subjects had sufficient serum vitamin 25(OH)D. It was found that vitamin D levels was inversely related with body weight (spearman r=-0.41, p=.003), fat free mass (spearman r:-0.51, p=.000) and basal metabolic rate (spearman r:-0.35, p=.012). We found no significant correlation between total calcium levels and any of the other parameters. Conclusion: In Turkish athletes, better cardiorespiratory fitness and lower percent of body fat were associated with higher serum 25(OH)D level. All these data were independent of serum total calcium level.